Medium Term Conservation of Several Carnation Accessions Via in Vitro Culture - Budiarto, Kurniawan; Marwoto, Budi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
Sufficient genetic diversity is important in carnation breeding program. In vivo conservation of carnation germplasmis considered inefficient due to some technical and economical aspects. In vitro conservation was then, expectedto overcome the limitation of in vivo method. The research was conducted to find out the proper media for medium-term in vitro conservation of several carnation accessions in low temperature storage. A complete factorialexperiment with 25 replications was designed to accomplish the combination of two factors. The first factor wassix commercial carnation cultivars, namely Pink Maladi, Orange Triumph, Opera, Tundra, Yellow Liberty and PradoReffit. The second factor was the conservation media i.e. 1⁄2MS + DMSO 3% and 1⁄2MS + 3% DMSO + 3% sucrose andcontrol (MS 0+3% sucrose). The results showed that in vitro conservation of carnation in low temperature weresuccessfully conducted using 1⁄2MS+3% DMSO and 1⁄2MS+3% DMSO+3% sucrose without significant variation in allaccessions tested up to 10 and 12 months respectively. The increase of death plantlets, however, was detected onthe media of 1⁄2MS+3% DMSO after 6 months storage with significant decrease in viability hereafter. The existenceof sucrose in DMSO media induced root formation and plantlet resistance to low temperature storage.